A Comparative Study between Swenson Abdominoperineal Pull-through and Transanal, Full Thickness, Swenson like Approach for Hirschsprung Disease - Mahmud, Khalid; Islam, MK; Alam, M Rashedul; Karim, Sabbir (Bangladesh Critical Care Journal, 2017)
Background: Hirschsprung disease (HD) is a congenital developmental disorder of intrinsic component of enteric nervous system leading to severe complication which needs operative correction. There are different operative techniques existing and each technique has its advantages and disadvantages. Objective: The aim of the study was to evaluate the better outcome between Transanal full thickness swenson like pull through and Swenson abdomino-perineal pull through. Method: The Prospective comparative study had been carried out in the department of paediatric surgery, Dhaka Shishu (Children) Hospital during the period of January 2014 to July 2016. Total 56 patients with HD patients were included in the study irrespective of colostomy except major co-morbidities which can influence the general outcomes and who did not agree to close stoma within 12 weeks of pull-through operation. Patients were allocated in both groups by purposing sampling. Twenty eight patients with long segment HD were allocated in Group-A and operated by Swenson abdominoperineal pull through and 28 patients with short segment disease were allocated in group-B and operated by Transanal, full thickness, swenson like procedure. Result: Among the study population 32 (57.14%) were male and 24 (42.86%) were female with age range was 1 day- 96 months. Four patients developed urinary incontinence, 3 patients developed cuff abscess and 2 patients developed fecal incontinence. And in group-B no patient developed urinary incontinence but 4 developed cuff and anastomotic abscess and no patient developed fecal incontinence. The mean operation time 114.14 ± 13.02 in group-A and 68.36 ± 16.12 minutes in group-B. Mean hospital stay in group-A was 6.18 ± 1.83 days and 5.05 ± 0.43 days in group-B. Conclusion: The newer modification, Transanal, full thickness Swenson like procedure can be better technique in the management of HD. Bangladesh Crit Care J March 2017; 5(1): 23-27